NICOLÁS DE RUEDA Y LA CONSTRUCCIÓN DEL NUEVO CIMBORRIO DE LA CASA DE COMEDIAS DE MURCIA (1747) - Pina Caballero, Cristina I. (Imafronte, 2008)
The old Casa de Comedias from Murcia was one of the main properties of the town council. Its maintenace and improvement was a continuous source of worry for municipal authorities. In 1747, Nicolás de Rueda. Architecture Headmaster of the town council, desinged new dome, and this proyect is the only in existence from the old theatre of Murcia.